PEMANFAATAN LIMBAH KULIT DAN PONGGE DURIAN DI KAMPUNG DURIAN MANTENAN DESA GIYANTI CANDIMULYO MAGELANG - Arifah, Siti; Nugraheni, Martha Arum; A’yun, Rizka Qurrota; Qurrota 'Aini, Saras Shinta (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Candimulyo District as a durian fruit center that has been famous since the 1980s, during the harvest season, attracts many people/visitors to come to enjoy this King of the fruits. Visitors come from various regions both domestically and abroad. This condition, in addition to providing a positive side in the form of increasing community income, on the other hand also raises problems in the form of piles of durian skin and pongge waste. The urgency of this community service activity is the utilization of durian skin and pongge waste as a form of effort to increase community income, especially in Giyanti Village, Candimulyo District, Magelang Regency. Durian skin and seeds waste that is currently not utilized and becomes a problem for the environment in Giyanti Village, in the form of an unclean environment that can cause environmental pollution and can affect the level of public health. With this activity, it is hoped that the existence of durian skin and seeds waste during the durian harvest season will not become a more widespread problem. The purpose of this community service activity is to improve the standard of living of the community through efforts to increase community income. Creativity and innovation are needed that can be done by the community to increase their income, including by utilizing existing potential. The role of academics is to transfer knowledge to the community through introduction and training related to handling the problems faced. The composition of the community service team consisting of food technology, nutrition, and accounting from Universitas Tidar is expected to provide optimal contribution to solving the problems in Giyanti Village, namely by utilizing durian skin and seeds waste into processed products that will encourage increased community income.